Teaching professors' challenges about community engagement outreach and intervention in Nigerian universities - Adekalu, Samuel Outokunbo; Krauss, Steven Eric; Ismail, Ismi Arif; Suandi, Turiman (Human Resource Management Academic Research Society, 2018)
Community engagement has been acknowledged as a core function of higher education, along with research and teaching which helps in promoting economic, environmental and socio-cultural development of communities. This article explores the barriers obstructing community engagement outreach and intervention in Nigerian higher education. Kwara State University, Malete, which adopted the philosophy of “the University for Community Development” is an interesting case in this study. Using in-depth semi-structured qualitative interviews, nine professors of the university were asked to reflect on how they sustained community engagement participation at different stages in their academic career. From data analysis, even though there are documentary evidences on the remarkable successes been achieved and reported with regards to community engagement activities and outreaches by the professors which helped to sustain professional identities and, in turn, career development. Four factors were found to be a barrier obstructing the professors’ participation in community engagement activities and outreaches. These were, (a) Educational gap between academics and community members, (b) lack of funds to execute community development projects, (c) time constraint due to multiple engagements, and (d) resistant to change by community members. The discussion and recommendations of this study are timely, as it concludes with a number of crucial issues that future community engagement in Nigerian higher education needs to be addressed.